AI and emerging filming technologies reshape the new driving force for the development of film and television art creation - Minjie Han; Yi Lan (SHS Web of Conferences)
AI (Artificial Intelligence) technology and new shooting techniques provide new research hotspots for the creation and development of film and television works.This academic conference is based on emerging technologies such as AI, VR (virtual reality), AR (augmented reality), MR(mixed reality), XR(extended reality),etc., and jointly explores the application and practical development prospects of AI and emerging shooting technologies in script conception, character shaping, scene construction, and post editing of film and television art creation.This study analyzed the advantages and disadvantages of emerging filming technologies in the film and television industry and proposed corresponding solutions, such as introducing intelligent editing, intelligent special effects, etc., to improve the efficiency and quality of film and television works. While bringing immersive viewing experience to the audience, it also promotes technological innovation and industrial upgrading in the film and television industry.The research results emphasize that the film and television industry must attach importance to talent cultivation and team building in its future development, strengthen communication and cooperation with AI technology enterprises, and jointly promote the research and development of emerging shooting technologies, providing a solid theoretical foundation, technical support, and practical reference for the future development of the film and television industry.